HUBUNGAN DURASI DUDUK DAN INDEKS MASSA TUBUH TERHADAP RISIKO DEEP-VEIN THROMBOSIS KARYAWAN - Shafia, Faiza; Wartono, Magdalena (Jurnal Biomedika dan Kesehatan, 2022)
Relationship between Sitting Duration and Body Mass Index to Deep-Vein Thrombosis Risk on Employee BACKGROUND Deep vein thrombosis (DVT) is a condition where a blood clot forms in the deep venous circulation system, especially in the femoral and popliteal vein. This disease has various factors, including obesity and a sedentary lifestyle such as sitting for long period of time. Employees who spend most of their time sitting at work are at risk of developing this condition. Previous studies showed different results, thus further research is needed. METHOD An analytic observational study with a cross-sectional method conducted on 90 employees at Bank BTN Head Office Jakarta from October to November 2021. Data were collected by interview using the OSPAQ questionnaire to assess sitting duration, Wells criteria to assess DVT risk, and calculation of body mass index (BMI). Sample was done by simple random sampling technique and analysis using chi-square. RESULTS There are more male respondents (60%) than female respondents (36%). It was found that 4,4% of employees have a thin BMI, 52,2% of employees have a normal BMI, and 43,3% of employees have a fat BMI. The respondents’ average sitting duration was 2,6 hours/day without interruption. There was no relationship between sitting duration (p=0,903) and the risk of DVT. There was a relationship between BMI (p=0,008) and the risk of DVT. CONCLUSION A body mass index above normal is a risk for deep vein thrombosis, but the disease is not affected by long sitting duration. Keywords : Sitting duration, Body mass index, Deep vein thrombosis, Employee